Hubungan Profitabilitas dan Ukuran Perusahaan terhadap Laporan Keuangan Menurut Persepsi Auditor - Cholis, Nur (UHAMKA Graduate School Thesis Abstract Collection, 2016)
The purpose of this study was to determine empirically the relationship profitability, and the size of the company to timely submission of financial statements according to the perception auditor. three hypotheses in this study 1) The Relationship Company Size Of Corporate Financial Reporting Auditor According perception. 2) The Relationship Profitability Against Corporate Financial Reporting Auditor According Perception 3) The Company's Relationship Profitability and Size jointly to the accuracy of financial reporting according to the perception of the auditor.This research was conducted in four public accounting firm that is Usman Saleh and Partners KAP, KAP Andiek Sumaryono and Partners, KAP Rica Angelina and Partners, KAP Jepta Silaban and Rekan.Sampel selected using purposive sampling and obtained a sample of respondents 32. Research data collection is done through questionnaires that have been in its validity and reliability.The method used is survey method with descriptive and associative approach because there are variables that will be explained and explored how big the influence of these variables. Statistical data analysis using non-parametric statistics using hypothesis testing, and t test.Of calculation hypothesis test and t test was concluded partially sized companies related to the timeliness of reporting the financial statements according to the perception of the auditor, while profitability is not related to the timeliness of financial reporting according to the perception of auditor, but with the same two variables are firm size and profitability related to the timeliness financial reporting according to the perception of the auditor.